PERENCANAAN DAN EVALUASI ANGGARAN SERTA STANDAR BIAYA PENGARUHNYA TERHADAP KINERJA ORGANISASI DI PEMERINTAH DAERAH KABUPATEN INDRAGIRI HILIR - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
This study aims to describe the effect of budget planning, budget evaluation and cost standards on organizational performance in the Regional Government of Indragiri Hilir Regency. This study uses quantitative methods with a causal research approach. The results of the study using multiple linear regression analysis based on the t test show that budget planning has a positive and significant effect on organizational performance, budget evaluation has a positive and significant effect on organizational performance and standard costs have a positive and significant effect on organizational performance.